1983
DOI: 10.3189/s0260305500005279
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and Analyses of Velocity Profiles and Frazil Ice-Crystal Rise Velocities During Periods of Frazil-Ice Formation in Rivers

Abstract: The vertical concentration distribution of frazil-ice crystals in a stream during the formation and gro~lth of frazil ice was discussed in a preliminary way by Gosink and Osterkal!1p (1981). This paper extends and completes the analysis of buoyant rise velocities of frazil-ice crystals and applies the results to an interpretation of measured velocity profiles in rivers during frazil-ice events. Additional experimental data are also presented. Two tillle scales are defined: the buoyant time scale TB, whi ch rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 9 publications
6
53
0
Order By: Relevance
“…This clearly portrays how small the volume of the plume is relative to that of the cavity. The velocity of the plume at the top of the cavity is 2.54 cm/s, which is much higher than the rise velocity of the crystals (2 mm/s, calculated along the lines described by Gosink and Osterkamp [1983]), justifying the assumption that the crystals are carried along with the plume until it reaches the top of the rift. Also, Figure 5 illustrates the profile of the rift's wall halfway through the integration and at its end.…”
Section: Standard Experimentsmentioning
confidence: 91%
“…This clearly portrays how small the volume of the plume is relative to that of the cavity. The velocity of the plume at the top of the cavity is 2.54 cm/s, which is much higher than the rise velocity of the crystals (2 mm/s, calculated along the lines described by Gosink and Osterkamp [1983]), justifying the assumption that the crystals are carried along with the plume until it reaches the top of the rift. Also, Figure 5 illustrates the profile of the rift's wall halfway through the integration and at its end.…”
Section: Standard Experimentsmentioning
confidence: 91%
“…S i represents the interaction terms between class i and other frazil size classes and therefore is a component of the release or uptake of water owing to the phase changes represented by the final term on the right-hand side of (2.4). The frazil rise velocity w i relative to the moving fluid is approximated by frazil's buoyant drift velocity in still water (Gosink & Osterkamp 1983): 8) where g = 9.81 m s −2 is the magnitude of acceleration due to gravity, a r is the aspect ratio of a frazil disk and r i is its radius. In this expression C d i is the crystal drag coefficient, which is calculated iteratively from the disk Reynolds number (JB).…”
Section: Frazil Governing Equationsmentioning
confidence: 99%
“…Gosink and Osterkamp (1983) reported frazil particle diameters ranging between 1 and 6 mm during a series of tests on the Chatanika River, Alaska. Chacho et al (1986) reported frazil diameters of 5 mm to 150 mm in the Tanana River.…”
Section: Frazil Particle Diameter (D) and Fall Velocity Coefficient (Cf)mentioning
confidence: 99%